Two adaptive rates of convergence in pointwise density estimation - Cristina Butucea (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
We consider density pointwise estimation and look for best attainable asymptotic rates of convergence. The problem is adaptive, which means that the regularity parameter, Ø, describing the class of densities, varies in a set B. We shall consider, successively, two classes of densities, issued from a generalization of L2 Sobolev classes: W (Ø, p, L) and M (Ø, p, L).
urn:nbn:de:kobv:11-10056124
Keywords: 330; nonparametric density estimation; adaptive rates; Sobolev classes